Barriers and facilitators to conducting human subjects research at a safety net institution from the perspective of researchers - Sarah J. Barnes; Yewon Na; Mari-Lynn Drainoni; Benjamin A. Linas; Nicholas A. Bosch; Autumn L. Tamlyn (PLoS ONE, 2025)
Introduction The COVID-19 pandemic revealed glaring problems with clinical research enterprise. Faced with crisis, several trials opened rapidly but enrolled homogenous populations with few Black, Indigenous, and People of Color (BIPOC) individuals. Inclusive trial enrollment is important to inspire trust and confidence in BIPOC populations that have been historically excluded or harmed from research and to improve the generalizability of research findings. Safety-net hospitals and institutions often care for BIPOC populations, and thus it is essential to improve equitable participation in research at these institutions. In this study, we sought to understand barriers and facilitators to research participation at safety net institutions. Methods We conducted semi-structured interviews among principal investigators, research assistants, research coordinators, and research nurses who conducted human subjects research at an urban, safety-net hospital from October, 2022 to December, 2022. We used inductive qualitative methods to identify themes associated with barriers and facilitators to clinical research participation. Results We completed 28 interviews and identified five themes: (1) compared to non-safety net systems, safety-net systems were perceived to require additional resources and funding to achieve comparable research recruitment and retention; (2) language barriers and translational processes are burdensome for researchers; (3) interactions between research staff and patients impact trust; (4) social determinants of health specific to safety-net populations are a barrier to participation; (5) competing priorities between clinical staff and researchers exist. Conclusion Safety net institutions face several barriers to conducting human subjects research. However, identified facilitators may help inform future efforts to reduce inequities in research participation.